Lieux et milieux dans le Théâtre de Béziers (XVIIe siècle) - Jean-François Courouau (Lengas)
The Theatre of Béziers brings together an ensemble of 24 published plays, performed in Béziers for the festival of Ascension between 1616 and 1647. These plays, composed entirely in Occitan or in a mix of Occitan and French, offer an ideal source of material for the analysis of interlanguage relationships. Using paratexts, stage directions and other information found in the works, it is possible to identify the locations where the action took place and, using toponyms mentioned in the texts, to recreate the geographic space that was offered to spectators. While the local setting is primordial (Béziers and its region), national references and beyond, to the edges of the known world, present an important openness to the world. The study extends to the socio-professional milieu of the characters. Not all are identified in terms of socio-professional status, but for those who are, we observe the strong presence of shepherds, connected to the pastoral convention and heavily invested in local agro-pastoral reality. Domestics, numerous in comedies, include rakish valets and loose chambermaids. The many soldiers present are an echo of contemporary difficulties (the Thirty Years War). They are generally presented as perturbing elements, as are the few ridiculed gentlemen, outcasts from the community.